PRACTICES OF SCHOOL HEALTH SERVICES IN PUBLIC AND PRIVATE SCHOOLS OF KARACHI CENTRAL - Dr Ume Amen; Dr Kiran Farooq; Dr. Aliza Naqvi; Rukhsana Haroon; Dr Ume Sumayya; Atif Aziz (International Journal of Contemporary Issues in Social Sciences, 2023)
The School Health Program (SHP) aims to promote healthy living practices from an early age, crucial in countries like Pakistan with high mortality rates. Originating from colonial America, SHP gained global recognition through WHO’s Global School Health Initiative. This research assesses SHS awareness among teachers in Karachi’s central district, proposing implementation guidelines. Through a quantitative survey of senior teaching staff from 30 schools, the study aims to enhance health education effectiveness. Findings reveal inadequacies in SHS practices, particularly regarding healthcare staff availability and health appraisals. Recommendations include increased healthcare staffing and government regulation in both public and private schools to ensure children’s health and safety.